2019
DOI: 10.30996/jmm17.v5i02.1947
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Gaya Kepemimpinan Transformasional, Karakteristik Individu, Lingkungan Kerja Terhadap Motivasi Kerja Dan Kinerja Guru SMK Negeri 1 Tambelangan Sampang

Abstract: The purpose of this study was to analyze the effect of the influence of transformationalleadership style, individual characteristics, work environment on work motivation and teacherperformance. The study was conducted at State Vocational School Tambelangan 1 , SampangRegency, with 40 teachers as respondents. Data collected with survey methode and questionnaireis as instrument. This research is included in associative research. The data obtained is analyzedusing SPSS. The results of the study were obtained, tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
1
4
1
2
Order By: Relevance
“…al (2020) found similar result that transformational principal correlated to work motivation of teachers. This finding is opposite to finding of study conducted by Soetopo et. al (2018) who found that principal's transformational leadership has no significance effect on the work motivation of teachers.…”
Section: Discussioncontrasting
confidence: 99%
“…al (2020) found similar result that transformational principal correlated to work motivation of teachers. This finding is opposite to finding of study conducted by Soetopo et. al (2018) who found that principal's transformational leadership has no significance effect on the work motivation of teachers.…”
Section: Discussioncontrasting
confidence: 99%
“…Motivation at work is described as something that raises encouragement or work enthusiasm or encourages work enthusiasm (Soetopo et al, 2019). motivation can also mean the drive to grow or emerge from within the individual who can provide strength and behavior in the work environment in carrying out his duties (Abdullah, Abdul Manan, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to research, the work environment and leadership style have a significant impact on work motivation (Anam, 2018;Efendi &;Hardiyanto, 2021;Hartinah et al, 2020;Soetopo et al, 2019;Yani, 2019). The conceptual framework created by the researcher is depicted in Figure 1.…”
Section: Concept Framework For Research and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…If a teacher has a high sense of motivation, then they will be encouraged to improve their ability to plan, implement and evaluate every lesson that has been implemented. The principal, as a leader, has a lead character that adapts to the school climate to drive school equipment so that institutional goals can be achieved (Soetopo et al, 2018;Royhatudin et al, 2020;Toyib et al, 2020). In addition to the leadership of the school principal, the school environment is also a factor that can affect employees' work productivity and effectiveness (Prihantoro, 2015).…”
Section: Introductionmentioning
confidence: 99%